Perancangan Learning Management System Berbasis Web Menggunakan Framework Codeigniter di Jakarta Global University (JGU) - Suprihadi, Untung; Alexander, Onki; Ekawati, Risma; Anggoro, Djatu (STMIK IKMI Cirebon, 2021)
Lack of motivation and student involvement in the learning process is a challenge in education today. This problem can be solved by e-learning method which combines forms of learning with communication, technology, motivation, effectiveness and efficiency. E-learning, online and digital based learning media, allows students to study anywhere at any time. Basically e-learning is only used for storing teaching materials. This kind of e-learning cannot motivate the learning process, to increase learning motivation, e-learning development must be carried out. The proposed solution is to expand the Learning Management System (LMS) in web-based e-learning by developing and adding several additional features to improve the effectiveness and quality of learning. This web-based e-learning adds to the features of lecturers and students in terms of communication and discussion, providing subject matter, assigning and collecting assignments online, providing information about values and campus activities, and also announcements too. With a design model that is easily accessible and not boring. To support this thesis, the method of data collection is done by observation, interviews, and literature study. This writing aims to develop a learning management system that can be accessed via internet, fully managed by administrators, used by lecturers, and also students. So that learning becomes precise, fast, and accurate.